Mycoplasma genitalium infections can comprise a mixture of both fluoroquinolone-susceptible and fluoroquinolone-resistant strains. (15th January 2021) - Sweeney, Emma L; Lowry, Kym; Bletchly, Cheryl; Nimmo, Graeme R; Whiley, David M
Abstract: Background: Mycoplasma genitalium was recently added to the CDC's antimicrobial resistance threats 'watch list', as it has rapidly become resistant to mainstay treatments. In Australia, treatment failure with fluoroquinolones remain commonplace, even when Sanger sequencing fails to identify evidence of resistance mutations. Methods: Suspecting that Sanger sequencing may miss low-load mixed infections, we applied three additional PCR-based approaches (allele-specific primer-based PCR, probe-based PCR and amplicon deep sequencing) to detect mutations associated with fluoroquinolone susceptibility/resistance. We focused on resistance mutations at amino acid positions 83 and 87 of parC, as these were previously shown to be common in Australia. Results: Our results showed evidence of mixtures of fluoroquinolone-susceptible and -resistant strains in up to 27/423 samples (6.4%). These included 1 sample that was indicated to be mixed by Sanger sequencing and all three additional PCR methods, 6 samples detected by two or more of the additional PCRs but not by Sanger sequencing and finally 20 samples that were detected by only one of the additional PCR methods. A key question was whether Sanger sequencing failed to detect fluoroquinolone resistance in any samples; overall, we observed that Sanger sequencing failed to detect fluoroquinolone resistance in up to 3.8% (16/423) of samples. Conclusions: The presence of mixed susceptibility infections may have important implications for clinical patient management and stresses the need for appropriate detection of resistance and selection of antimicrobials to ensure appropriate treatment of M. genitalium infections.